Carbohydrate antigen 19-9 for differential diagnosis of pancreatic carcinoma and chronic pancreatitis - Su, Si-Biao (World J Gastroenterol, 2015)
AIM: To evaluate the utility of carbohydrate antigen 19-9 (CA19-9) for differential diagnosis of pancreatic carcinoma and chronic pancreatitis. METHODS: We searched the literature for studies reporting the sensitivity, specificity, and other accuracy measures of serum CA19-9 levels for differentiating pancreatic carcinoma and chronic pancreatitis. Pooled analysis was performed using random-effects models, and receiver operating characteristic (ROC) curves were generated. Study quality was assessed using Standards for Reporting Diagnostic Accuracy and Quality Assessment for Studies of Diagnostic Accuracy tools. RESULTS: A total of 34 studies involving 3125 patients with pancreatic carcinoma and 2061 patients with chronic pancreatitis were included. Pooled analysis of the ability of CA19-9 level to differentiate pancreatic carcinoma and chronic pancreatitis showed the following effect estimates: sensitivity, 0.81 (95%CI: 0.80-0.83); specificity, 0.81 (95%CI: 0.79-0.82); positive likelihood ratio, 4.08 (95%CI: 3.39-4.91); negative likelihood ratio, 0.24 (95%CI: 0.21-0.28); and diagnostic odds ratio, 19.31 (95%CI: 14.40-25.90). The area under the ROC curve was 0.88. No significant publication bias was detected. CONCLUSION: Elevated CA19-9 by itself is insufficient for differentiating pancreatic carcinoma and chronic pancreatitis, however, it increases suspicion of pancreatic carcinoma and may complement other clinical findings to improve diagnostic accuracy.